New Insights Into the Skin Microbial Communities and Skin Aging - Li, Zichao; Bai, Xiaozhi; Peng, Tingwei; Yi, Xiaowei; Luo, Liang; Yang, Jizhong; Liu, Jiaqi; Wang, Yunchuan; He, Ting; Wang, Xujie; Zhu, Huayu; Wang, Hongtao; et al. (Frontiers in Microbiology, 2020)
Although it is well-known that human skin aging is accompanied by alteration in the skin microbiota, we know little about of how the composition of this changes during the course of aging and the effects of age-related skin microbes on aging. Using 16S rDNA and ITS rDNA sequencing to profile the microbiomes of 160 skin samples from two anatomical sites, the cheek and the abdomen, on 80 individuals of varying ages, we developed age-related microbiota profiles for both intrinsic skin aging and photoaging to provide an improved understanding of the age-dependent variation in skin microbial composition. According to the landscape, the microbial composition in the Children group was significantly different from that in the other age groups. Further correlation analysis with clinical parameters and functional prediction in each group revealed that high enrichment of nine microbial communities (i.e. Cyanobacteria, Staphylococcus, Cutibacterium, Lactobacillus, Corynebacterium, Streptococcus, Neisseria, Candida, and Malassezia) and 18 pathways (such as biosynthesis of antibiotics) potentially affected skin aging, implying that skin microbiomes may perform key functions in skin aging by regulating the immune response, resistance to ultraviolet light, and biosynthesis and metabolism of age-related substances. Our work re-establishes that skin microbiomes play an important regulatory role in the aging process and opens a new approach for targeted microbial therapy for skin aging.